Exploring the Well-Being of Adolescents with Developmental Disabilities through the Lens of Filipino Families - Candelario, Sarah Grace L. (Alipato, A Journal of Basic Education; Vol 15 (2024): Alipato, A Journal of Basic Education, 2025)
Well-being, which encompasses quality of life, life satisfaction, and happiness, is locally understood as 'kaginhawaan' or 'kagalingan'. In special education, the concept of well-being is not clearly defined among families with members who have developmental disabilities. Hence, this multiple case study sought to determine how Filipino families perceive the well-being of adolescents with developmental disabilities (ADDs). Through purposive sampling, seven families and their ADD were selected as participants of this study. Qualitative data was gathered through interviews and field observations. Data analysis involved two levels of analysis that began with a within-case analysis of each family unit. Then, through cross-case synthesis, further thematic analysis was conducted by aggregating findings from each family case. The results revealed nine themes that represent family perceptions on the well-being of their ADD. These perspectives include: (1) being provided lifelong support by the family, (2) learning functional life skills, (3) being productive despite the disability, (4) being independent despite limitations, (5) living with dignity despite the disability, (6) addressing health and safety independently, (7) experiencing belongingness and being included in the community, (8) raising own family beyond limitations of disability, and (9) developing spirituality and trusting in God’s provisions despite the challenges of the disability. These were utilized to contextualize the concept of well-being that includes dimensions that Filipino families regard as important for their ADD’s lifelong well-being. The study advocates for the provision of special education and creation of individualized transition plans (ITPs) informed by the dimensions of well-being that were identified and prioritized by Filipino families to ensure relevant goal-setting and effective instruction to support the lifelong well-being of ADDs.